MLIF Modulates Microglia Polarization in Ischemic Stroke by Targeting eEF1A1 - Yulan Liu; Yulan Liu; Shanshan Deng; Zhibing Song; Qian Zhang; Yuchen Guo; Yongsheng Yu; Yuliang Wang; Tiejun Li; Fayed A. K. Megahed; Tamer A. Addissouky; Junqin Mao; et al. (Frontiers Media S.A., 2021)
Monocyte locomotion inhibitory factor (MLIF) is a heat-stable pentapeptide from Entamoeba histolytica. Our previous study found that MLIF protects against ischemic stroke in rats and mice and exerts a neuroprotection effect in human neuroblastoma SH-SY5Y cells. Microglia/macrophage polarization has been proven to be vital in the pathology of ischemic stroke. Nevertheless, whether MLIF is able to modulate microglia/macrophage polarization remains unclear. We performed middle cerebral artery occlusion (MCAO) on C57BL/6J male mice and induced cultured BV2 microglia by oxygen-glucose deprivation (OGD), respectively. Immunfluorescence was utilized to detect the M1/2 markers, such as CD206 and CD16/32. qPCR and ELISA were used to detect the signature gene change of M1/2. The MAPK and NF-κB pathway associated proteins were measured by Western blot. To identify the protein target of MLIF, a pull-down assay was performed. We found that MLIF promoted microglia transferring from a "sick" M1 phenotype to a "healthy" M2 phenotype in vivo or in vitro. Furthermore, we proved that eukaryotic elongation factor 1A1 (eEF1A1) was involved in the modulation of microglia/macrophage polarization. Knocking down eEF1A1 by siRNA exhibited the M1 promotion effect and M2 inhibition effect. Taken together, our results demonstrated MLIF modulated microglia/macrophage polarization by targeting eEF1A1 in ischemic stroke.